Некоторые математические модели геоинформатики для описания процессов переноса в условиях временной нелокальности - Булавацкий, В.М. (Проблемы управления и информатики, 2011)
Побудовано узагальнені математичні моделі нелокальних у часі процесів масо- та теплопереносу в пористих середовищах. Отримано аналітичні розв’язки деяких крайових задач теорії геофільтрації, поставлених у рамках запропонованих математичних моделей. The generalized mathematical models for time-nonlocal processes of mass and heat transfer in porous mediums are constructed and the analytical solutions of some boundary value problems of the theory of a geofiltration put within the frame of the offered mathematical models are received.